EVOLUTION OF SYSTEMIC JUVENILE ARTHRITIS DURING LONG-TERM FOLLOW-UP - Svetlana Olegovna Salugina (Научно-практическая ревматология, 2012)
Objective: to study the evolution of systemic juvenile arthritis (JA) in adult patients. Subjects and methods. The trial covered 19 patients (7 men, 12 women; mean age 28.8+9.1 years) with systemic JA who had fallen ill in childhood (at the age of 1 to 16 years). The duration of the disease was 11 to 53 years (mean 24.7+11.4 years). Its systemic manifestations at the onset included fever (n = 18), rash (n = 8), lymphadenopathy (n = 7), hepatolienal syndrome (n = 8), pericarditis (n = 1). At the onset, oligoarthritis was present in 9 (47.4%) patients; polyarthritis was in 7 (36.8%) and 3 patients had only arthralgies. Results and discussion. The rate of systemic manifestations was decreased over the course of the disease and they were detected only in 3 patients by the moment of the trial. At the examination, almost half (n = 9) had no active arthritis, 10 had inflammatory changes in the joints. At the trial, the total scores of inflammatory disease activity were retained in the vast majority (n = 17); however, its magnitude was low or modest. The mean HAQ score was 1.2. More than half of the patients had retarded physical development or disproportionate body build. X-ray changes were absent or minimal in 4 patients; there were erosions in 5, ankyloses in 3, and Stage IV sacroiliitis in 2. Six patients presented with aseptic necrosis of the heads of the femur and humerus. Nine patients received nonsteroidal anti-inflammatory drugs; 7 took glucocorticoids, and 7 had disease-modifying anti-rheumatic drugs, mainly methotrexate. At the study, the disease activity steadily remained low in 5 patients; 1 patient achieved complete remission; an exacerbation was seen in 13 of the 19 patients. 5-to-23-year remissions were recorded in 11 (57.9%) patients over the course of the disease. Conclusion. The patients with long-term JA tend to develop polyarthritis. Despite the severity, remaining inflammatory activity, and recurrent course of arthritis, the magnitude of its systemic and articular manifestations is reduced in most patients over time. During the disease, there may be long-term remissions; however, one third of the patients develop an erosive process and almost half do aseptic necrosis, which is the ground to continue active therapy.